EP 43. MUNIX measurements in ALS patients as clinical routine procedure in a specialized neuromuscular treatment unit. Issue 9 (September 2016) - Ringer, T.M.; Appelfeller, M.; Gunkel, A.; Prell, T.; Stubendorff, B.; Witte, O.W.; Großkreutz, J.
Abstract : Introduction: Amyotrophic lateral sclerosis is characterized by progressive motor neuron degeneration. Different motor unit number estimations methods were described in the last years to quantify the underlying motor unit decline. However these methods are time-consuming and did not find their way into clinical routine. Recently, motor unit number index (MUNIX) as a fast new technique was introduced, relying on surface interference patterns (SIP) recorded during voluntary isometric contractions. Recent studies demonstrated already a decline of motor unit index values during disease progression comparable to the ALS functional rating score in a scientific environment where variability was diminished by intense rater training. Objective: Our goal was to implement MUNIX as routine procedure in a specialized neuromuscular unit under realistic medical care conditions, to determine variability and benefit in clinical routine in ALS patients. Methods: MUNIX-measurement were performed prospectively in 73 ALS patients cross-sectional in up to four muscles (APB, ADM, TA, EDB) in our neuromuscular unit by trained raters. In addition, in a patient subset repeated measurements during disease progression were performed as well and quality parameters were obtained. Results: MUNIX values were significantly reduced in ALS patients versus controls (APB 56, 6 ± 50, 7 [mean ± SD] vs. 163, 9 ± 56, 2; ADM 64, 1 ± 0, 8 vs. 126, 4 ± 29, 5; EDB 42, 8 ± 32, 6 vs. 85, 2 ± 44, 0 and TA 77, 5 ± 40, 4 vs. 124, 5 ± 38, 7) and showed marked variability. Quality markers improved initially during the study and were then stable in an acceptable range. Linear regression analysis showed a marked correlation of MUNIX values with CMAP amplitudes. However, MUNIX values did not correlate to total ALSFRS-R-Score, cervical respectively lumbar ALSFRS-subscores nor disease duration in our cohort. Conclusion: MUNIX measurements in clinical routine show marked variability, which cannot be eliminated completely by intense rater training and may complicate interpretation of single MUNIX values in clinical routine. However, decreased MUNIX values can be detected independently of ALSFRS-R-subscores and may be helpful surrogate markers especially in repetitive measurements during ALS progression. Acknowledgment: This research is supported by BMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID) and JPND (SOPHIA) of the European Union and was undertaken in collaboration with the German MND-NET.